The softest sound levels of the human voice in normal subjects - Šrámková, Hana; Granqvist, Svante; Herbst, Christian T; Švec, Jan G (The Journal of the Acoustical Society of America, 2015)
Accurate measurement of the softest sound levels of phonation presents technical and methodological challenges. This study aimed at (1) reliably obtaining normative data on sustained softest sound levels for the vowel [a:] at comfortable pitch; (2) comparing the results for different frequency and time weighting methods; and (3) refining the Union of European Phoniatricians' recommendation on allowed background noise levels for scientific and equipment manufacturers' purposes. Eighty healthy untrained participants (40 females, 40 males) were investigated in quiet rooms using a head-mounted microphone and a sound level meter at 30 cm distance. The one-second-equivalent sound levels were more stable and more representative for evaluating the softest sustained phonations than the fast-time-weighted levels. At 30 cm, these levels were in the range of 48-61 dB(C)/41-53 dB(A) for females and 49 - 64 dB(C)/35-53 dB(A) for males (5% to 95% quantile range). These ranges may serve as reference data in evaluating vocal normality. In order to reach a signal-to-noise ratio of at least 10 dB for more than 95% of the normal population, the background noise should be below 25 dB(A) and 38 dB(C), respectively, for the softest phonation measurements at 30 cm distance. For the A-weighting, this is 15 dB lower than the previously recommended value.
Keywords: Acoustics; Transducers; Adolescent; fonace; Time Factors; lidé středního věku; Signal Processing, Computer-Assisted; lidé; hluk; časové faktory; Adult; Signal-To-Noise Ratio; Middle Aged; dospělí; počítačové zpracování signálu; Phonation; Calibration; akustika; kvalita hlasu; Female; Reference Values; kalibrace; Male; ženské pohlaví; Voice Quality; mladý dospělý; poměr signál - šum; referenční hodnoty; Humans; měniče; mužské pohlaví; Young Adult; Noise; mladiství